Marché foncier et évolution des usages et des valeurs de la terre agricole à Regueb (Tunisie) - Mathilde Fautras (VertigO)
As in many other countries, the Tunisian government has been initiating a politics of individualization of the agricultural land management for several decades. The regime of tribal communal land, which was predominant in the centre and the south of the country, has been replaced by a regime of individual private ownership. This change has induced important impacts on the rural areas : agrarian changes and the development of a located land market, as in the region of Regueb, where the transactions involve foreign-born protagonists since the 1990s. The aim of this article is to understand the process of land commodification, by analysing the land market “local system of actors”, and the relationships between this system and the evolution of the uses and the values of a land. This article is based on a fieldwork research carried out between 2012 and 2014 in the region of Regueb. It shows how the capitalist logics contribute to the recomposition of this rural area and to weakening of the land rights of the peasants. This weakening is partially caused by some experienced entrepreneurs and speculators, who better know the inner workings of this capitalist system, including some people having a long story of land appropriation in the Sfax hinterland. At the same time, the capitalist logics remain mixed to endogenous social logics, where the economic dimension doesn’t strongly determine the social life. The current social and economic marginalization of a part of the peasants results both from economic and politic domination relationships, and from endogenous material and immaterial factors which slow down the expansion of capitalism.